A Tutoring Start-Up in COVID-19 Emergency: Lessons Learned - Gallagher-Mackay, Kelly; Corso, Christine; Manion, Carly; Ta, Tina; Tam, George; Mundy, Karen (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2026)
This action research study examines a university-school board virtual tutoring program developed as an emergency response during the COVID-19 pandemic to support disadvantaged students in Ontario, Canada—a distinctive and underexamined governance context within the global tutoring literature. Situating tutoring as a policy response that circulated internationally during the pandemic, the study evaluates academic and social-emotional impacts using performance data, surveys, tutor reflections, and self-assessments. Positive social-emotional outcomes and strong administrative support marked program successes, while academic gains were limited. The analysis identifies emergency program design features—including limited frequency, after-school delivery, and technical and institutional constraints—as key barriers to academic impact. The study contributes to comparative and international education research by examining how a globally circulating policy response was translated within a decentralized, risk-averse public education system, highlighting implications for equity, innovation, and university-school board partnerships. As public investments in tutoring expand internationally, the findings underscore the importance of context-responsive program design in education-in-emergencies settings.